Strategi Bertahan Hidup Pengemudi Ojek Online (Studi Pada Pengendara Maxim Motor di Kota Gorontalo) - Rahmatiah; Hatu, Dewinta Rizky R.; Pomantolo, Fasila (Program Studi Sosiologi, Fakultas Ilmu Sosial Universitas Negeri Gorontalo, 2024)
The current transformation in the utilization of online motorcycle taxi services, particularly Maxim, has shifted societal paradigms in leveraging these services to support daily activities. However, the dilemma arising from the mismatch between the nature of work and the income outcomes for Maxim drivers in Gorontalo City has sparked new debates and simultaneously posed challenges that require attention. This research aims to analyze the strategies employed by online motorcycle taxi drivers, specifically Maxim riders in Gorontalo City, focusing on three strategic approaches: active, passive, and networking strategies. The research methodology utilized in this study is qualitative. Twelve Maxim drivers and one employee from the Maxim office in Gorontalo City were involved as informants. Data collection techniques included observation, interviews, and documentation. The research findings reveal three main points. Firstly, drivers proactively seek additional opportunities, optimize working hours, and take initiatives to enhance their earnings. Secondly, passive strategies are also preferred by Maxim drivers in addressing economic challenges and competition. With a more relaxed approach and selective order management, they reduce risks and costs while striving to maintain reasonable income. Thirdly, networking strategies play a crucial role in Maxim drivers' efforts to survive. Building strong relationships with fellow drivers, business partners, and customers enables mutual support, information sharing, and business expansion. In conclusion, the collectively adopted strategies by Maxim drivers demonstrate their consistency in meeting primary and secondary needs. Their strategic choices reflect a multifaceted approach in addressing the challenges and opportunities presented by the dynamics of online motorcycle taxi services.